FinTech Risks in Indonesia - Ratih Kusumastuti, Derist Touriano (International Conference on Industrial Revolution for Polytechnic Education, 2019)
The current phenomenon in Indonesia is a shift in consumer behavior, from conventional services to information technology-based services that grow and develop so rapidly that it opens opportunities for start-up companies utilizing FinTech. But the Financial Services Authority (OJK) is currently aware of the main risks of FinTech-based financial services. From this phenomenon is the main reason to examine more deeply the high risk of FinTech services with research problems that will be examined in this study is what risks most significantly affect FinTech services in Indonesia.This study uses an explanatory method in order to explain the risk of FinTech services as measured by objective and empirically standardized tools. This research data was obtained from the first party (primary) by using survey techniques for explaining the symptoms, problems, and objects under study. The population of the study is an auditor who works on 600 KAP registered under the auspices of the Indonesian Accountants Association (IAI) by using a convenience sampling method. Further, while serenteristics that will be observed, manipulated, controlled in this study are security, availability, performance and compliance risk for FinTech services. While data processing uses SPSS 22 tools to test data quality and describe the risk ranking statistics for FinTech services in Indonesia based on a 7-point Likert scale.The risk rating for FinTech services in Indonesia derived from the results of data analysis revealed that the five major components of risk that greatly impacted FinTech services were 1) inadequate capacity management, 2) controls, 3) Institution factors, 4) ICT system failures and 5) authentication. The five main risks, 4 risks are included in the dimensions of availability risk and 1 risk including security risk so that it can be interpreted that the risk of FinTech services in Indonesia tends to be in accordance with the results of research by Tchernykh et al. (2016)where most of the vendors or FinTech providers in Indonesia do not consider the unavailability of systems or hardware components so that in the event of an emergency, they are unable to restore services in a timely manner. Besides that, the main risks that often occur are cheating or an attacker's attempt to exploit IS/IT security loopholes that have an impact on the financial loss of its users.Risk ranking is an advanced stage after identifying risks at FinTech services, this aims to determine the degree of risk that will occur or that will be faced by the company / its users. In addition, companies can prioritize the most important risks so as to accelerate their handling and minimize greater losses in the future. It is hoped that in the future risk-related research and FinTech will need to be continuously assessed according to the rapid innovation in the IS / IT field and the threat of cyberwar in the digital era